(untitled) (Global Journal of Science Frontier Research, 2018)
Determination of the activity of a 1.10-Phenanthroline compound as an agent of anti UV was measured using a UVVis spectrophotometer. The study of the electronic transition of 1.10-Phenanthroline compounds was carried out computationally with the semi-empirical of ZINDO/s method. The results of determining the potential of the 1.10-Phenanthroline compound as an anti UV radiation agent showed the lowest%Te value of 0.102%, the highest SPF value of 2.328 and the lowest%Tp value of 0.509%. The type of transition found in 3 peaks in the 1.10-Phenanthroline compound shows the transition types; n to π ⃰ and π to π ⃰ . Whereas, molecular orbitals (MO) involved in electron excitation were: 32 (HOMO-1), 33 (HOMO), 34 (LUMO) and 35 (LUMO + 1) with the smallest energy difference value being 33 to 34 excitation of 7.78 eV.